Determinação da eficiência de irrigação ao nível de parcela, no projeto de irrigação bebedouro — Petrolina, Pernambuco - Pereira Leal, Marcos Vinícios; Bernardo, Salassier; Bernardes Coelho, Mauricio; Pereira, Paulo Afonso (Revista Ceres, 2025)
The objective of this study was to determine the efficiency of irrigation in the Bebedouro Irrigation Project in Petrolina, Pernambuco. The irrigation method in use in this project is furrow irrigation with a constant flow rate.